Nonoperative Treatment of Medial Ulnar Collateral Ligament Injuries in the Throwing Athlete: Indications, Evaluation, and Management. Issue 1 (January 2019) - Kadri, Omar M.; Okoroha, Kelechi R.; Patel, Ravi B.; Berguson, Jon; Makhni, Eric C.; Moutzouros, Vasilios
Abstract : Ulnar collateral ligament (UCL) injuries are common in overhead throwing athletes, particularly baseball players. Appropriate diagnosis, treatment, and rehabilitation are important in order for athletes to return to their preinjury condition. Many patients, including the noncompetitive athletes and those with partial ligament tears, benefit from nonoperative treatment. Elite athletes desiring a return to play benefit from UCL reconstruction. Rest, anti-inflammatory drugs, focused physical therapy, and biologic adjuncts are options that may allow athletes to return to play while avoiding the morbidity associated with operative treatment.